Perancangan dan Pembuatan Sistem Informasi Akademik Berbasis Web Menggunakan Framework Codeigniter dan Mysql - Mohamad Wahyu Dewantoro; Madiyanto Mardiyanto (STT Cahaya Surya Kediri, 2018)
Current technological developments are increasingly rapid, marked by increasingly integrated technology in various aspects of our lives, one of them in the aspect of education. At present, along with the development of technology, the role of technology in education is getting stronger, one of which is the application of Information Systems in Education, namely the Academic Information System. Where academic information systems are systems that manage all activities related to academic activities, such as learning processes, assignments, examinations, grades, management of students and teachers, graduation and alumni. A good School Academic Information System is a system that can achieve satisfaction from users, which in this case are prospective students, students, teachers, stakeholders, and parents so that all can feel the impact of the information system that can improve the quality of graduates from their schools.